Guinea : Economic Development Documents. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Guinea's 2016-20 National Economic and Social Development Plan (PNDES). The PNDES represents the second generation of planning under the Third Republic, after the 2011-15 Five-Year Plan. Through the 2016-20 PNDES, the authorities intend to address the various development challenges posed by the socioeconomic and environmental situation while ensuring post-Ebola public health surveillance and alignment with international development agendas. The principal beneficiaries of the PNDES are the Guinean populations, but particularly poor and vulnerable groups, the government itself, the private sector, and the regions, including urban and rural areas.